The Evaluation of Partnership Method in the Business in Indonesia - Mikha Valeo; Richard Ham (Journal of International Conference Proceedings (JICP), 2018)
This research aims to analyze how to build a business connection using partnership based on coordination method using PT. Nipsea & Chemicals as the example. PT.Nipsea & Chemicals use a very effective partnership method that we will explain in the later part of this paper, it needs to be conducted because of the crowded competition of businesses nowadays. In order to analyze the method, data will be collected by survey and observation. Then data will be analyzed and compared to the product development method using descriptive quantitative research. We aims to take the positive aspects and get rid of the negative aspects from both of the methods and create a better method that willmake more profits, and assuring a stable relationship with the customers.